Appendicitis: Trends In Age, Sex And Seasonal Variations In Pediatric Surgery Ward Of Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2014)
Appendicitis is a common clinical condition worldwide. Differences in incidences, age, sex and seasonal variations have been reported widely. To assess the trends in percentage (%) and variation with age, sex and seasons of the year. A review of the 5 years records (January 2008 to December 2012) of all patients with appendicitis treated in pediatric Surgery ward of Chittagong Medical College Hospital (CMCH) was evaluated. The age, sex and months of admission for all the cases of appendicitis were analyzed. There were 576 cases of appendicitis during the study period. Male to female ratio was 2.8:1. A continuous increase in number was noticed over the years and the number in 2012 was almost one and half times that of 2008. There were fewer cases in 2-5 years age group (38) and more in 6-12 years age group (538). Percentages of cases were higher in the period between October and December with peaks in October and March; and declining from the month of July. There is an increasing number of appendicitis in children in Chittagong Medical College Hospital. Appendicitis occurs more in early winter. Boys suffer more than the girls and 6-12 years is the commonest age of appendicitis.JCMCTA 2013 ; 24 (2): 26-29